Pengaruh Pendampingan Gizi terhadap Perubahan Perilaku Pemenuhan Gizi Ibu Hamil Kurang Energi Kronik (KEK) - Demsa Simbolon; Antun Rahmadi; Jumiyati Jumiyati (Politeknik Kesehatan Tanjung Karang, 2019)
CEDs in pre-pregnancy and pregnant women have an impact on the birth of Intra Uterine Growth Retardation (IUGR) children, Low Birth Weight (LBW) and stunting, so that SEZ problems in pregnant women need to be improved through nutritional assistance. The study aims to prove the effect of nutritional assistance on CED pregnant women on changes in knowledge, attitudes and actions in fulfilling nutrition. The study was carried out in the cities of Bengkulu and Bandar Lampung with a quasi-experimental design carried out by health cadres who had been trained to assist pregnant women with CED to carry out health promotion and monitor consumption of Supplementary Feeding Programme (SFP) and Fe Tablet consumption for 3 months. Changes in knowledge, attitudes and actions in nutritional fulfillment were analyzed by different mean and independent samples. The results of the study found that effective nutrition assistance to increase knowledge, positive attitudes and actions of CED pregnant women in fulfilling nutrition. After mentoring there was a significant increase in the average knowledge score, attitudes and actions of CED pregnant women in both the City of Bengkulu and in Bandar Lampung. Need continuous nutrition assistance for CED pregnant women so that behavioral changes and fulfillment of balanced nutrition occur during pregnancy and postpartum.